The influence of footwear on the windlass mechanism and toe movement - Tanaka, Satoshi; Hasegawa, Masaki; Otsuka, Akira; Shimatani, Koji; Kanai, Shusaku; Oki, Sadaaki; Shimizu, Mischele Eisemann (Structure and Function, 2007)
The purpose of this study was to investigate the effects of footwear on the metatarsophalangeal joint (MP joint) and medial arch during gait. Ten healthy subjects participated in the experiment. We measured the angle of the MP joint and medial arch during gait while wearing geta or shoes or barefooted. A three-dimensional motion analysis system was used to evaluate toe and arch movements (120 Hz) . The MP hyper-extension and medial arch angle was correlated, so called windlass mechanism. Shoes limited MP hyper-extension, so the medial arch angle was limited too. But Geta only limited the MP angle. The medial foot arch was maintained by ligaments, bone alignment, intrinsic muscles etc. We concluded that the intrinsic muscles were active during Geta gait. Because the toe flexor muscles fixed the Geta to the foot, the medial arch angle increased. A previous study reported that it is important to exercise the toes to prevent foot disorders. Geta may be useful for foot health.